Project management, planning and control : managing engineering, construction and manufacturing projects to PMI, APM and BSI standards - Lester, Albert (Butterworth-Heinemann, an imprint of Elsevier, 2017)
Building on its clear and detailed coverage of planning, scheduling and control, this seventh edition includes new advice on information management, including big data, communication, dispute resolution, project governance, and BIM. Ideal for those studying for Project Management Professional (PMP) qualifications, the book is aligned with the latest Project Management Body of Knowledge (PMBOK) for both the Project Management Institute (PMI) and the Association of Project Management (APM), and includes questions and answers to help users test their understanding
Keywords: projektový management; project management; příručky; handbooks and manuals